PERANCANGAN SISTEM INFORMASI MANAJEMEN PROYEK DENGAN MENGGUNAKAN SOFTWARE NEST.JS BERBASIS WEB DI PT. MITRA PAJAKKU - Acep Muhamad Saepuloh; Seliwati Ginting (POLITEKNIK PIKSI GANESHA, 2022)
This study aims to analyze, design and build a management information system at PT. Mitra Pajakku. The research method used is descriptive qualitative method. Data collection techniques used are literature study, observation and interview. Software development method used is Exterme Programming. From the research conducted, it was found that the process of monitoring a task or task on a project or product is due to the current information system being less supportive and some still using manual records. Therefore, a system management information system was designed using the Web-based Nest.Js software. The system designed and built has the features of recording tasks per project, timeline and sprints. As for some suggestions given in dealing with the problem, namely 1) introducing the application, 2) replacing the information system designed by the author, 3) direct testing of the application, 3) developing report features, 4) developing import features.